Technique failure in peritoneal dialysis-related peritonitis: risk factors and patient survival - Jin Yu; Lingli Zhu; Jun Ni; Mengli Tong; Hua Wang (Renal Failure, 2023)
Objective This study aimed to investigate the association between patient clinical characteristics and technique failure in peritoneal dialysis-related peritonitis (PDRP). The effect of peritonitis-associated technique failure on patient survival was also assessed.Methods Patients diagnosed with PDRP from January 1, 2010 to June 30, 2022 were retrospectively reviewed and analyzed. Relevant demographic, biochemical, and clinical data were collected. Univariate and multivariate logistic regression analyses were used to determine the predictors of peritonitis-associated technique failure in PD. Patients were divided into technique failure (F group) and nontechnique failure (NF group) groups. Patients were followed until death or until the date of Oct 1, 2022. Kaplan–Meier survival curves and landmark analysis were used to assess the survival of the PDRP cohort. Cox regression models were used to assess the association between potential risk factors and mortality.Results A total of 376 patients with 648 cases of PDRP were included in this study. Multivariate logistic regression analysis demonstrated that peritoneal dialysis (PD) duration (OR = 1.12 [1.03, 1.21], p = 0.005), dialysate WBC count on Day 3 after antibiotic therapy (OR = 1.41 [1.22, 1.64], p = 0.001), blood neutrophil-to-lymphocyte ratio (NLR) (OR = 1.83 [1.25, 2.70], p = 0.002), and serum lactate dehydrogenase (LDH) (OR = 4.13 [1.69, 10.11], p = 0.002) were independent predictors for technique failure in PDRP. Furthermore, serum high-density lipoprotein (HDL) (OR = 0.28 [0.13, 0.64], p = 0.002) was a protective factor against technique failure. According to the Kaplan–Meier analysis, patients experiencing peritonitis-associated technique failure had lower postperitonitis survival (log-rank = 4.326, p = 0.038). According to the landmark analysis, patients with a history of peritonitis-associated technical failures had a higher 8-year mortality after peritoneal dialysis. A Cox model adjusted for plausible predetermined confounders showed that technique failure was independently associated with all-cause mortality.Conclusions Dialysate WBC count on Day 3, PD duration, NLR, and LDH were independent risk factors for technique failure, whereas HDL was a protective factor. Peritonitis-associated technique failure had a higher risk of mortality and adverse effects on postperitonitis survival.